Synthesis, complexion and reactivity studies of novel bis (1,2,3-triazol-5-ylidene) carbazolide ligands - Bezuidenhout, Daniela Ina (University of Pretoria, 2022)
Dissertation (MSc)--University of Pretoria, 2014.